Integritas Struktur Alas Prostetik Pergelangan Kaki dengan Bahan Baja dan Aluminium - Handoko; Lilik Dwi Setyana; Budi Basuki; Setyawan Bekti Wibowo; Bambang Hari Priyambodo; Yani Kurniawan; Rizky Kurniawan (Universitas Proklamasi 45, 2025)
Leg prosthetics support the mobility of people with disabilities. Designing economical leg prosthetics is a major challenge for increasing accessibility for disabled people because the majority of them are from low income economy. Technically, the challenge is to make a cheap buat light weight prosthetics. Low cost metal raw material of prosthetics are often inversely proportional to the weight of components. One of the cheap materials, i.e. steel has a specific gravity 2.9 times higher than aluminum, which is lightweight but twice as expensive. This study examines the structural integrity of ankle prosthetic base components made of steel and aluminum when subjected to dynamic loads of the human body in a single step, using finite element method numerical computations. The goal is to determine whether the type of cheap material will be reliable in bearing the load. The computational results show that inexpensive materials such as mild steel and aluminum 6061 are able to support the mechanical structure of ankle prosthetic model to remain rigid while handling dynamic loads. The working stresses of both materials are still within safe limits, able to bear the load, even when multiplied by safety factor, the stresses are still below the yield stress value of each material. Aluminum 6061 is recommended for the production of lightweight versions of prosthetic models due to its maximum deflection that is really small as low as 4.41 x 10-3 mm, while mild steel is for the low-cost versions. Validation of the computational results was carried out using comparative literature data. Contact pressure value of 3 MPa from this research is in accordance with literature.